Pregnant women's social representations and decisions about delivery: women's protagonism - Pereira, Raquel da Rocha; Franco, Selma Cristina; Baldin, Nelma (Saúde e Sociedade, 2011)
The main objective of this study was to understand, based on female social representations, women's protagonism concerning the decision about child delivery. Through a qualitative research with a phenomenological approach, forty-five pregnant women were interviewed in the last quarter of pregnancy. They were receiving prenatal care at the public and private health systems of the city of Joinville, state of Santa Catarina (Southern Brazil). The analysis of the content of the narratives revealed three empirical categories: fears and worries; experiences; and sociocultural influence. With this theoretical and methodological substratum, it was possible to analyze the women's social representation during the process of delivery, which is symbolized by conflicts of feelings, doubts and apprehension derived mainly from fear of the suffering imposed by pain. Such conception is supported by the biomedical model and by the media. In Brazil, delivery, which is almost "outsourced", is culturally understood as a complex stage that requires specialized knowledge. This legitimizes the technical-scientific knowledge to the detriment of physiological knowledge, reinforcing the asymmetry of the power of decision between doctor and pregnant woman. Besides, the pregnant women's lack of knowledge about the meaning, the impact and the benefits of the delivery stage for the newborn baby makes them insecure and without critical sense about the content of other information sources, such as soap operas, other pregnant women's stories built by the social environment, and their own experience in previous deliveries. This generates a behavior marked by doubts and apprehension. Fragile, these women submit themselves to a programmed cesarean section to avoid physical and emotional pain caused by fear. Reversing this situation involves a review of the doctor's education and actions of women's empowerment.